(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
Consensus tracking control problem of the multi-agent systems with both noise and disturbances is studied in this paper. A robust adaptive control scheme is designed according to Lyapunov stability theory. The main contribution of this paper is that the consensus is realized in multi-agent systems with both noise and external disturbances. Numerical simulations are carried out for the proposed scheme to demonstrate the effectiveness of the control strategy proposed in this paper.